Sex difference in the association of metabolic syndrome with high sensitivity C-reactive protein in a Taiwanese population - Lin Wen-Yuan; Liu Chiu-Shong; Kardia Sharon LR; Li Chia-Ing; Lai Ming-May; Lee Yih-Dar; Chang Pei-Chia; Lin Cheng-Chieh; Li Tsai-Chung (BMC, 2010)
Abstract Background Although sex differences have been reported for associations between components of metabolic syndrome and inflammation, the question of whether there is an effect modification by sex in the association between inflammation and metabolic syndrome has not been investigated in detail. Therefore, the aim of this study was to compare associations of high sensitivity C-creative protein (hs-CRP) with metabolic syndrome and its components between men and women. Methods A total of 1,305 subjects aged 40 years and over were recruited in 2004 in a metropolitan city in Taiwan. The biochemical indices, such as hs-CRP, fasting glucose levels, lipid profiles, urinary albumin, urinary creatinine and anthropometric indices, were measured. Metabolic syndrome was defined using the American Heart Association and the National Heart, lung and Blood Institute (AHA/NHLBI) definition. The relationship between metabolic syndrome and hs-CRP was examined using multivariate logistic regression analysis. Results After adjustment for age and lifestyle factors including smoking, and alcohol intake, elevated concentrations of hs-CRP showed a stronger association with metabolic syndrome in women (odds ratio comparing tertile extremes 4.80 [95% CI: 3.31-6.97]) than in men (2.30 [1.65-3.21]). The p value for the sex interaction was 0.002. All components were more strongly associated with metabolic syndrome in women than in men, and all sex interactions were significant except for hypertension. Conclusions Our data suggest that inflammatory processes may be of particular importance in the pathogenesis of metabolic syndrome in women.